2005
DOI: 10.1074/jbc.c500044200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Pantothenate Kinase Isoform from Helicobacter pylori

Abstract: Pantothenate kinase (PanK) catalyzes the first step in the biosynthesis of the essential and ubiquitous cofactor coenzyme A (CoA) in all organisms. Two well characterized isoforms of the enzyme are known: a prokaryotic PanK that predominates in eubacteria and a eukaryotic isoform that has primarily been characterized from mammalian and plant sources. Curiously, the genomes of certain pathogenic bacteria, including Helicobacter pylori and Pseudomonas aeruginosa, do not contain a PanK similar to either isoform, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 25 publications
1
95
1
Order By: Relevance
“…The type III BsPanK also exhibited a five-to-six-fold increase in K m (Pan) relative to EcPanK and SaPanK; this correlates with the observation that N5-Pan is neither an alternate substrate for nor a competitive inhibitor of BsPanK. Limited bioinformatics analyses suggested that both type II and type III PanKs belonged to the ribonuclease H-like family [kinase family and fold group 4 (15)] of kinases (18). Very recently, Hong et al (19) and Yang et al (20) have confirmed these predictions with crystal structures for the type II SaPanK-AMPPNP complex and for the type III PanKs from Pseudomonas aeruginosa (PaPanK) and Thermotoga maritima (TmPanK), as well as the PaPanK-Pan complex.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The type III BsPanK also exhibited a five-to-six-fold increase in K m (Pan) relative to EcPanK and SaPanK; this correlates with the observation that N5-Pan is neither an alternate substrate for nor a competitive inhibitor of BsPanK. Limited bioinformatics analyses suggested that both type II and type III PanKs belonged to the ribonuclease H-like family [kinase family and fold group 4 (15)] of kinases (18). Very recently, Hong et al (19) and Yang et al (20) have confirmed these predictions with crystal structures for the type II SaPanK-AMPPNP complex and for the type III PanKs from Pseudomonas aeruginosa (PaPanK) and Thermotoga maritima (TmPanK), as well as the PaPanK-Pan complex.…”
supporting
confidence: 52%
“…In 2005, the bacterial type II and type III PanKs were identified in S. aureus (17), and in Helicobacter pylori and Bacillus subtilis (18), respectively. Neither isoform is similar in sequence to the type I EcPanK, nor is either subject to feedback inhibition by CoASH.…”
mentioning
confidence: 99%
“…These genes do not share sequence similarity (39), but they, nonetheless, encode enzymes that catalyze the same reaction. The enzyme encoded by coaA is of type I, whereas the enzyme encoded by coaX is a type III enzyme (39,40). The existence of the alternative coaX explains the low genome occurrence of coaA, but it also reinforces the essentiality of the reaction.…”
Section: Genes Responsible For Superessential Reactions Occur In Mostmentioning
confidence: 99%
“…Experiments using lysate provide a useful tool for studying phosphorylation independently of transport but do not take into account the regulation of phosphorylation in situ. CoA and/or its esters have been shown to inhibit the PanKs of bacteria, plants, and animals (1), although recently the PanKs from Staphylococcus aureus and Helicobacter pylori have been shown to be refractory to this feedback inhibition (29,30). We therefore investigated the effects of CoA on PfPanK activity.…”
Section: Pantothenol Uptake By Isolated Parasites Is Ph-dependent-mentioning
confidence: 99%